Selfie addiction: the prodigious self-portraits - Nagalingam, Saranya; Arumugam, Balaji; Thenniz Preethy, S. P. (International Journal of Research in Medical Sciences, 2019)
Background: Selfie’s are self-portrait taken to admire the excessive pride in one’s own appearance. When these selfies are taken persistently in increased numbers with futile efforts to stop taking them is called as “SELFIE ADDICTION”. There is an uncontrollable craving for taking selfie’s which has a great impact on the life style modifications substantially in the adolescent age group. This problem has just commenced but it has disseminated rapidly to a greater magnitude. Methods: This study was done as a community based cross sectional study at Pondicherry, Chennai and Kadaloor district during November 2015 and February 2016 with the objectives of assessing the prevalence and its risk factors of the Selfie addiction among adolescents. Individuals of adolescent age group were randomly selected and the data were collected using direct questionnaire method with proper informed consent. The data was entered in MS excel sheet and analysis was done using SPSS software. Results: A total of 766 college students were interviewed of which 53% were males with the mean age of 19 years. The purposes of taking selfies were time pass (46%), to admire themselves (14.5%), to post in social network sites (23.7%). Among the study participants 87% of them had the habit of taking selfies regularly using mobile phones and the number of selfies per minute varied from 2 to 10 per minute. The prevalence of selfie addiction was present among 111 (14.5%) and it was significantly associated with gender, higher version mobile phone users, early morning selfie takers, chronic mobile users. Conclusions: The prevalence of selfie addiction among adolescent population in our study was moderately high and hence interventions should be made to create cognizance among the general population about the risk factors and its consequences.